2011
DOI: 10.4177/ccgp-d-11-00015.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chemical Reagents on Rheological Properties of Fly Ash-Water Slurry at Varying Temperature Environment

Abstract: About 70% of total electrical energy is generated from thermal power plants in India which in turn release about 160 Mt of fly ash as solid waste annually. Transportation and disposal of such a huge amount of fly ash is a major problem faced by the power plants. Presently fly ash is transported as lean slurry in pipe lines requiring about 80 to 85% of water with high energy input. A major impediment in high volume transportation of fly ash is its high specific gravity as compared to that of water. The objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…The addition of the cationic and the counter ions reduces the surface tension with the aim of enhancing the suspension strength in particulates. An increase in the wetting and spreading properties is found which results in low power/water requirements [10]. Senapati et al [11] investigated the fly/bottom ash slurries to predict the effects of friction on the concentrated slurry.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of the cationic and the counter ions reduces the surface tension with the aim of enhancing the suspension strength in particulates. An increase in the wetting and spreading properties is found which results in low power/water requirements [10]. Senapati et al [11] investigated the fly/bottom ash slurries to predict the effects of friction on the concentrated slurry.…”
Section: Introductionmentioning
confidence: 99%
“…Naik et al (2009aNaik et al ( , 2009bNaik et al ( , 2011 studied the effects of addition of Cetyl Trimethyl Ammonium Bromide and Sodium Salicylate on the rheological Properties of FA-water suspensions for 20% to 40% concentration at temperature ranging from 20 to 40 0 C and found that the viscosity and shear stress decreased for all the cases with increase in temperature and the slurry without additive showed shear thickening behaviour but exhibited almost Newtonian pattern with a zero yield stress when the concentration of the additive solution increased gradually with an incremental value of 0.1% by mass. According to their investigation the effective additive concentration range was found to be from 0.2% to 0.3% by mass.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The polymer Separan AP-302 was injected into pipeline (up to 60 wppm) and observed increasing of concentration and pipeline load capacity represented 22% drag reduction effect. The effect of addition of chemical reagents on rheological flow behavior of ash slurry was studied by some researchers (Vlasak and Chara, 2007;Seshadri et al 2008;Naik et al 2011;Senapati et al 2012;Singh and Lal, 2012). It was indicated that the additive modified the rheological behavior of the ash slurry at high solids concentration and the ash slurry viscosity got reduced with improved flow behavior.…”
Section: Introductionmentioning
confidence: 99%